‘The More We Stand For – The More We Fight For’: Compatibility and Legitimacy in the Effects of Multiple Social Identities - Chayinska, Maria; Minescu, Anca; McGarty, Craig (Frontiers in Psychology, 2017)
This paper explores the expression of multiple social identities through coordinated collective action. We propose that perceived compatibility between potentially contrasting identities and perceived legitimacy of protest serve as catalysts for collective action. The present paper maps the context of the “Euromaidan” anti-regime protests in Ukraine and reports data (N = 996) collected through an online survey following legislation to ban protests (March – May, 2014). We measured participants’ identification with three different groups (the Ukrainian nation, the online protest community, and the street movement), perception of compatibility between online protest and the street movement, perception of the legitimacy of protest, and intentions to take persuasive and confrontational collective action. We found evidence that the more social groups people “stood for”, the more they “fought” for their cause and that identifications predicted both forms of collective action to the degree that people saw the protest and the online movement as compatible with each other and believed protest to be legitimate. Collective action can be interpreted as the congruent expression of multiple identities that are rendered ideologically compatible both in online settings and on the street.